Saussurea costus (Falc.) Lipsch.: a comprehensive review of its pharmacology, phytochemicals, ethnobotanical uses, and therapeutic potential - Kumari, Ruchika; Negi, Madhvi; Thakur, Palak; Mahajan, Himadri; Raina, Kirti; Sharma, Rohit; Singh, Randeep; Anand, Vikas; Long, Chiau Ming *; Goh, Khang Wen; Calina, Daniela; Sharifi-Rad, Javad; et al. (Springer, 2024)
Saussurea costus (Falc.) Lipsch., commonly known as costus, is a perennial herb that has been traditionally used in various indigenous medicinal systems across Asia. Its historical prominence in traditional remedies underscores the need to explore its phytochemical composition, pharmacological properties, and potential therapeutic benefits. This review aims to provide a comprehensive overview of the available literature on the pharmacological properties, phytochemical constituents, ethnobotanical uses, and therapeutic potential of S. costus. An exhaustive search was performed across multiple electronic databases, including PubMed/MedLine, Google Scholar, Web of Science, Scopus, TRIP database, and Science Direct. Both experimental and clinical studies, as well as traditional ethnobotanical records, were considered for inclusion. The phytochemical analysis revealed that S. costus contains a plethora of bioactive compounds, including sesquiterpenes, flavonoids, and essential oils, which are responsible for its myriad of medicinal properties. The pharmacological studies have demonstrated its anti-inflammatory, anti-oxidant, anti-cancer, hepatoprotective, and immunomodulatory effects, among others. Ethnobotanical data showcased its extensive use in treating ailments like asthma, digestive disorders, and skin conditions. Some clinical trials also underscore its efficacy in certain health conditions, corroborating its traditional uses. S. costus possesses significant therapeutic potential, largely attributable to its rich phytochemical composition; the convergence of its traditional uses and modern pharmacological findings suggests promising avenues for future research, especially in drug development and understanding its mechanism of action in various ailments.